Cidade do desapego: o estar-queer na urbanidade contemporânea - Vieira, Marcos Sardá (2018)
Although current cities are conceived by an idea of normality of actions and behaviours, this whole structure of comfort and material attachments also leads to a consensual imprisonment which makes sedentary the search for a more contemplative and pleasurable life for most city dwellers. From my experience on errant journeys through Berlin and other European cities this thesis is presented as a cartography sewn by fundamental relations between gender, space and sexuality. These themes arise through the interdisciplinary relationship between applied social sciences and human sciences being crossed by theories of gender and Queer Theory in particular. In this research I sought to explore the concept of being-queer as a potency of articulation of body, desire and conscious/itinerant thinking, bringing possibilities to the experiences of detachment, deconstructing absolute stays and opening renewed paths to rethink the urbanity of the metropolises in a more creative way.